2007
DOI: 10.1002/jso.20811
|View full text |Cite
|
Sign up to set email alerts
|

Combined brief psychosexual intervention after mastectomy: Effects on sexuality, body image, and psychological well‐being

Abstract: CBPI can be used as an effective alternative to individual or group psychotherapy for mastectomy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 38 publications
2
107
0
10
Order By: Relevance
“…Interventions were grouped into two categories according to their main therapeutic approach: 'Cognitive Behavioural Skills Training' (CBST) (n=25), which focuses on illness cognitions, education, goal setting, and coping strategies such as problem solving and symptom management; and 'Relationship Counselling' (RC) (n=10), which addresses relationship difficulties such as sexual intimacy, partner supportiveness, and communication [38,51,45,52,53,54,55,56,57,58]. There was no noticeable effect of mode of delivery (faceto-face, telephone, online) on illness type or outcomes.…”
Section: Intervention Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions were grouped into two categories according to their main therapeutic approach: 'Cognitive Behavioural Skills Training' (CBST) (n=25), which focuses on illness cognitions, education, goal setting, and coping strategies such as problem solving and symptom management; and 'Relationship Counselling' (RC) (n=10), which addresses relationship difficulties such as sexual intimacy, partner supportiveness, and communication [38,51,45,52,53,54,55,56,57,58]. There was no noticeable effect of mode of delivery (faceto-face, telephone, online) on illness type or outcomes.…”
Section: Intervention Outcomesmentioning
confidence: 99%
“…When compared with a patient-only or control group, interventions based on RC were most effective at addressing interpersonal issues including relationship satisfaction [52,54], perceived partner acceptance of self-image [54], communication quality [56], marital functioning [57], and dyadic adjustment [58]. Intimacy [53] and sexual communication and distress [58] were more effectively targeted by RC.…”
Section: Effect Of Rc On Patient/ Partner Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most intervention studies addressing sexual adjustment in couples are theoretical in nature (Badr & Krebs, 2013;Canada, Neese, Sui, & Schover, 2005;Kalaitzi et al, 2007;McCorkle, Siefert, Dowd, Robinson, & Pickett, 2007). Consequently, there is a need for a theoretical framework to inform programmaticresearchandto facilitatethedesignofinterventions.…”
Section: Introductionmentioning
confidence: 99%
“…Canada, Schover, and Li (2007) found that adolescents and young adults with cancer who received psychosexual counseling experienced improved body image and decreased anxiety about sexual and romantic relationships. Further, a study among mastectomy patients showed significant improvement in depression and state-anxiety scores as well as in body image, satisfaction with relationship, presumed attractiveness to their partner, orgasm frequency, and communicating their desire (Kalaitzi et al, 2007). Other researchers have used a psychotherapy similar to psychosexual therapy that was shown to be effective for people with a variety of disorders (Himelhoch, Medoff, & Oyeniyi, 2007;Schramm et al, 2008).…”
mentioning
confidence: 99%